Fresno's Martin Luther King, Jr. March from City Hall to Saroyan Theatre - Watkins, Howard::::::::: (1987)
Major Dale Doig speaking in front of City Hall at 2326 Fresno Street Chris Petersen, Mary Curry, Karen Humphrey and Les Kimber standing